2021
DOI: 10.2174/0929867327999200819123357
|View full text |Cite
|
Sign up to set email alerts
|

Pieces of the Complex Puzzle of Cancer Cell Energy Metabolism: An Overview of Energy Metabolism and Alternatives for Targeted Cancer Therapy

Abstract: Over the past decades, several advances in cancer cell biology have led to relevant details about a phenomenon called "Warburg effect". Currently, it has been accepted that Warburg effect is not anymore compatible with all cancer cells, and thus the process of aerobic glycolysis is now challenged by the knowledge of a large number of cells presenting mitochondrial function. The energy metabolism of cancer cells is focused in the bioenergetic and biosynthetic pathways to meet the requirements of rapid prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 176 publications
1
2
0
Order By: Relevance
“…We confirmed that lipid metabolism-related lncRNAs may serve as a signature for predicting survival Energy metabolism reprogramming is an important feature of tumors [21,22]. The imbalance among oncogenic pathways interferes with the synthesis and metabolism of various substances, including glucose, glutamine, and fatty acids, thereby promoting the growth of tumor cells [23][24][25]. To date, studies on the association of lncRNA expression with lipid metabolism in colon cancer are scarcely reported.…”
Section: Discussionsupporting
confidence: 71%
“…We confirmed that lipid metabolism-related lncRNAs may serve as a signature for predicting survival Energy metabolism reprogramming is an important feature of tumors [21,22]. The imbalance among oncogenic pathways interferes with the synthesis and metabolism of various substances, including glucose, glutamine, and fatty acids, thereby promoting the growth of tumor cells [23][24][25]. To date, studies on the association of lncRNA expression with lipid metabolism in colon cancer are scarcely reported.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, it is also suggested that the underlying mechanism of the pro-oxidant effect of melatonin on cancer cells involves the inhibition of HIF-1α by melatonin. HIF-1α is a key transcription agent involved in mediating Warburg-type metabolisms in diseased cells [ 62 , 63 ]. HIF-1α is also part of an oxygen sensing system that is activated when the partial pressure (pO 2 ) of intracellular oxygen becomes depressed.…”
Section: Involvement Of Molecular Pathways In Melatonin’s Pro-oxidati...mentioning
confidence: 99%
“…Within a given solid tumor there may be a gradient from near the center of the tumor where the oxygen tension is lowest to the periphery where the cells may be normoxic; this is also reflected in the intensity of HIF-1α expression [ 104 , 105 , 106 , 107 ]. Unequivocally, HIF-1α has a central role in orchestrating the processes that allow cancer cells (and other diseased cells) to accommodate aerobic glycolysis [ 108 , 109 ]. Under normoxic conditions, in which most cells exist, HIF-1α subunits are ubiquitinated by the von Hippel–Landau complex and quickly undergo proteasomal degradation, so it has little effect on glucose metabolism or oxidation [ 110 , 111 ].…”
Section: The Warburg Effect: a Focal Point For A Number Of Diseasementioning
confidence: 99%